Proceso de atención de enfermería en paciente con embarazo ectópico de 6 semanas de gestación - Alvarado Rezabala, Katiusca Alexandra (2021)
An ectopic pregnancy is a serious complication that occurs in pregnancy, where the fertilized egg goes to develop in the tissues of the uterine wall. Either by implantation in the fallopian tubes, ovary, cervical canal, pelvic cavity and even in the abdominal cavity. This clinical picture studies the case of a 21-year-old patient with a 6-week gestation ectopic pregnancy, who came to the hospital emergency room due to moderate transvaginal bleeding, syncope, and contraction-type hypogastric pain that radiates to the area. lumbar of moderate intensity. The physical assessment is carried out and the dysfunctional patterns that are compromising the patient's health status are identified, in order to develop the Nursing Care Process in order to develop a care plan related to the needs required by the patient. . Adequate treatment, comfort and follow-up will also be provided. In the same way, the pertinent nursing care will be carried out, applying the use of the taxonomies Nanda, Nic, and Noc in order to fulfill our objectives proposed in this clinical case study.